MAULANA JALALUDDIN RUMI'S POEMS OF LONGING AS A SOURCE OF INSPIRATION FOR PAINTINGS - Islam, Mohamad Fajarudin; Susanto, Moh. Rusnoto; Susanto, Dwi; Barriyah, Insanul Qisti; Finanda, Septy Asri (International Journal of Engagement and Empowerment (IJE2), 2024)
The artist attempts to visualize the value and philosophical meaning of Maulana Jalaluddin Rumi's poems of longing. The message and meaning in Maulana Jalaluddin Rumi's longing poems will be the primary foundation in the artist's interpretation process, focusing on the value of love and longing to be realized as a means of visual communication through painting. The method of creating this final project is also an attempt to learn the artist's creativity, ideas, and techniques to express themselves through a painting and produce works that represent the artist. The method used by the artist in the creation process includes observation, Exploration, design, and realization of the work. The artist observes and absorbs the values and meanings contained in Maulana Jalaluddin Rumi's poems of longing through a source in the form of books, literary works, the internet, and philosophical studies about Maulana Jalaluddin Rumi. To support the process of creating this painting, the artist also explores by observing the works of previous artists and visiting art galleries. The results of these processes become the artist's capital to carry out a method of realization of the painting. The artist visualizes the idea in a painting, with eight paintings sourced from the artist's Exploration. The resulting artworks have sizes ranging from 100x80 cm to 120x100 cm. All the artworks were then exhibited and presented to the examiners